Transfected Babesia bovis Expressing a Tick GST as a Live Vector Vaccine. - Daiane P Oldiges; Jacob M Laughery; Nelson Junior Tagliari; Ronaldo Viana Leite Filho; William C Davis; Itabajara da Silva Vaz; Carlos Termignoni; Donald P Knowles; Carlos E Suarez (Public Library of Science (PLoS), 2016)
The Rhipicephalus microplus tick is a notorious blood-feeding ectoparasite of livestock, especially cattle, responsible for massive losses in animal production. It is the main vector for transmission of pathogenic bacteria and parasites, including Babesia bovis, an intraerythrocytic apicomplexan protozoan parasite responsible for bovine Babesiosis. This study describes the development and testing of a live B. bovis vaccine expressing the protective tick antigen glutathione-S-transferase from Haemaphysalis longicornis (HlGST). The B. bovis S74-T3B parasites were electroporated with a plasmid containing the bidirectional Ef-1α (elongation factor 1 alpha) promoter of B. bovis controlling expression of two independent genes, the selectable marker GFP-BSD (green fluorescent protein-blasticidin deaminase), and HlGST fused to the MSA-1 (merozoite surface antigen 1) signal peptide from B. bovis. Electroporation followed by blasticidin selection resulted in the emergence of a mixed B. bovis transfected line (termed HlGST) in in vitro cultures, containing parasites with distinct patterns of insertion of both exogenous genes, either in or outside the Ef-1α locus. A B. bovis clonal line termed HlGST-Cln expressing intracellular GFP and HlGST in the surface of merozoites was then derived from the mixed parasite line HlGST using a fluorescent activated cell sorter. Two independent calf immunization trials were performed via intravenous inoculation of the HlGST-Cln and a previously described control consisting of an irrelevant transfected clonal line of B. bovis designated GFP-Cln. The control GFP-Cln line contains a copy of the GFP-BSD gene inserted into the Ef-1α locus of B. bovis in an identical fashion as the HIGST-Cln parasites. All animals inoculated with the HlGST-Cln and GFP-Cln transfected parasites developed mild babesiosis. Tick egg fertility and fully engorged female tick weight was reduced significantly in R. microplus feeding on HlGST-Cln-immunized calves. Collectively, these data show the efficacy of a transfected HlGST-Cln B. bovis parasite to induce detectable anti-glutathione-S-transferase antibodies and a reduction in tick size and fecundity of R. microplus feeding in experimentally inoculated animals.